Pengaruh Gaya Komunikasi dan Pesan Komunikasi Dokter UGD Terhadap Kepuasan Pasien Pada Rumah Sakit Islam Siti Hajar Mataram - Nugraha, Lalu Anugrah; Hidayat, Dasrun; Mulyani, Kahar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The research titled "The Influence of Communication Style and Communication Messages of Emergency Room Doctors on Patient Satisfaction at Siti Hajar Islamic Hospital Mataram" is based on numerous complaints regarding patient satisfaction with the communication style of doctors in the emergency room (ER). Communication between doctors and patients often triggers dissatisfaction, as expectations do not match the outcome. This study aims to analyze the influence of communication style and communication messages of ER doctors on patient satisfaction. The research method used is quantitative analytical with a cross-sectional approach. The research sample was taken based on accidental sampling. The findings of the study show a significant influence of the communication style of ER doctors on patient satisfaction, the communication messages of ER doctors on patient satisfaction, and collectively, both the communication style and communication messages of ER doctors on patient satisfaction, with a satisfaction percentage of 84.2%. The remaining 15.8% of patient satisfaction is influenced by other factors, such as short waiting times to receive medical services and the smoothness and speed of the medical service process experienced. The implications of this research explain that good communication by ER doctors has a positive impact on patient satisfaction at the hospital.